IMPLEMENTATION OF DRIVE-THRU SERVICE POLICY IN THE ONE-STOP MANUNGGAL ADMINISTRATION SYSTEM (SAMSAT) RABA BIMA - Abdullah Abdullah (DIA: Jurnal Administrasi Publik, 2023)
Policy implementation is a problem faced in implementing a policy or rule, both policies that include social problems and other problems. This research aimed to analyze how the implementation of the One-Stop Manunggal Administration Drive-Thru service policy (SAMSAT) Raba Bima and to determine the level of community satisfaction after the existence of the Raba Bima One-Stop Manunggal Administration Drive Thru (SAMSAT) service. This research used a descriptive approach with informants in this research employees of Samsat Raba Bima, SAMSAT Drive Thru officers in the community who pay taxes at SAMSAT Drive Thru. The results of this research are to use indicators, communication, resources and dispositions as well as rules in measuring the community satisfaction index. With the conclusion of the research, the implementation of the SAMSAT Drive Thru service policy has not been maximized with several obstacles and problems faced in service delivery. The SAMSAT Drive Thru service is intended only in the legal area of SAMSAT Raba Bima, and is still in charge of BANK NTB after seven years of Drive Thru until now.